Teaching and learning of Mandarin as a foreign language in South African schools - Norma Nel (Perspectives in Education, 2016)
Globalisation has influenced the demand for the acquisition of Mandarin. As a proactive response, the South African Department of Education included Mandarin as a second additional language in the National Curriculum Statement grades R–12 in March 2015. The research reported on in this article was context specific. It entailed a case study of a school in Gauteng that had introduced Mandarin as a foreign language. Chomsky’s language theory, the interactionist theory and Vygotsky’s socio-cultural theory are acknowledged. A qualitative inquiry strategy was employed; individual and focus group interviews, questionnaires and observations were used as data gathering tools. Content analysis was done manually. Themes, categories and subcategories were identified. The research culminated in a case study narrative elaborating on the main themes, namely motivation and beliefs, teaching Mandarin, and learners’ learning experiences.